Implementation of Sustainable Development Policies in Waste Management - Lia Muliawaty; Rizky Ilhami (Journal of Governance, 2022)
The balance between the environment and development must also be considered by the government so that the community in the future will not be affected by the development carried out. One way of implementing development is to conduct sustainable development that is environmentally sound. One of the sustainable development policy issues is in terms of waste management. Therefore, this study aims to analyze the implementation of sustainable development policies in the city of Bandung, especially in terms of waste management. This study uses qualitative methods with data collection carried out through observation, interviews and literature study. Data analysis includes data collection, data reduction and presentation of analytical data with descriptive methods. The results show that the waste management policy in Bandung City refers to regulations at the central and regional levels where in its application these policies are not in accordance with Law No. 18 of 2018 because it leads to waste as a source of regional income. Therefore, a sustainable development policy in waste management is developed by considering 4 strategic aspects, namely environmental, economic, social and technical aspects.